The cloud in Al-Sayyab’s poetry and its significance - فاضل ياسر; فاخر ميا; محمد مروشية (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The symbol of the cloud is associated with the poets with the symbol of rain and what it carries of goodness, giving and growth; However, sometimes it has been associated with misery and misery, as it represented birth, revolution, and purification with the rain that it carries, washing and purifying what falls on it.The reader will notice that many of the expressions used by the early Arabs to describe clouds and rain are still used with the same meanings and connotations to this day.Poets of all ages excelled in depicting natural scenes, including the description of the cloud and rain, which they carried many connotations that differed from one poet to another. Part of it used, while the other part of it became extinct.As for Al-Sayyab, the symbol of the cloud was abundant in his poetry, accompanied by the symbol of rain. Which we mentioned pains that filled the poet’s chest and made him sad and tired, so the symbol of the cloud came with many connotations different from what the poets who preceded him mentioned at one time, and similar to what they mentioned at another time.